Does The Fraud Pentagon Theory Effectively Detect Financial Statement Fraud? - Putri Sari (Postgraduate Program Merdeka University, 2024)
This study aims to assess and evaluate the effectiveness of the Fraud Pentagon Theory in identifying fraudulent financial statements. The independent va-riables used in this study are Leverage, Inadequate monitoring, auditor turn-over, change of directors, and frequent number of CEOT Related to this, this study focuses on financial sector companies listed on the Indonesia Stock Exchange in 2018 to 2022, because financial sector companies are more vul-nerable to fraud. The sample approach used is purposive sampling. Based on the specified criteria, the sample consists of 55 results obtained from 11 com-panies in the financial industry. The data analysis methodology used a logistic regression model to assess its feasibility. The research findings indicate that leverage substantially impacts the prevalence of financial statement fraud. However, factors such as inadequate monitoring, auditor turnover, board turnover, and the number of CEO photo frequencies did not show a signi-ficant influence on financial statement fraud.DOI: https://doi.org/10.26905/afr.v7i2.12710Â Â